HUBUNGAN LAYANAN ASUHAN KEPERAWATAN OLEH PERAWAT PELAKSANA DENGAN KEPUASAN PASIEN DI RUANG RAWAT INAP SAKURA RUMAH SAKIT UMUM IMELDA PEKERJA INDONESIA MEDAN - Imelda Liana Ritonga; Muhammad David (Jurnal Ilmiah Keperawatan IMELDA, 2020)
ABSTRACT Measuring customer satisfaction is an important element in providing better, more efficient and more effective service. If a customer is dissatisfied with a service provided, then the service can be ascertained that it is ineffective and inefficient. This is especially important for public services. The implementation of services to the community, as carried out by the Imelda Indonesian Worker Hospital in Medan, needs to get attention, especially in the quality of service to suit the needs and expectations of the community. This study focuses on the quality of nursing services and patient satisfaction in the Sakura Room Hospital Imelda Hospital Medan inpatient. This study aims to determine the Nursing Care Services by Implementing Nurses with Patient Satisfaction in the Sakura Inpatient Room Imelda General Hospital Indonesian Workers Medan. This research uses descriptive correlation research with a cross sectional approach, while the data analysis used is the Spearman Spirit correlation statistical test. The population in this study were patients who were treated in the Sakura Room inpatient installation of RSU IPI Medan, namely 31 patients who were hospitalized. The number of samples of 31 respondents by means of purposive sampling. The results showed that the quality of nursing services at Inpatient Intalasi IPI Hospital was 20 respondents (64.5%), 6 respondents (19.4%) sufficient category and 5 people (16.1%) in poor category. The conclusion is that there is a relationship (r = 0.615) between closing nursing services and patient satisfaction, where the higher the quality of nursing service, the higher the patient satisfaction.